Comparing Acoustic Tag Attachments Designed for Mobile Tracking of Hatchling Sea Turtles - Hoover, Aimee L.; Shillinger, George L.; Swiggs, Jennifer; Bailey, Helen (Frontiers in Marine Science, 2017)
The poorly understood movements of sea turtles during the ‘lost years’ of their early life history have been characterized as a ‘passive drifter’ stage. Biologging technology allows us to study patterns of dispersal, but the small body size of young life stages requires particular consideration that such tagging does not significantly impede animal movements. We tested the effect of instrument attachment methods for mobile acoustic tracking of hatchling sea turtles, including a design that would be suitable for leatherback turtles (Dermochelys coriacea). We obtained 8-week-old hatchery-reared green sea turtles (Chelonia mydas) (n = 12 individuals) and examined the effect of attaching Vemco V5 acoustic tags. Each animal’s swim speed, swimming depth, and stroke frequency were determined under three scenarios: control, direct Velcro® attachment to the carapace, and harness attachment, to determine if there was a significant difference amongst treatments. Turtle swimming speed was significantly slower during the middle period of the trial for the harness attachment compared with the control. No significant change in swim speed was observed when the tag was attached directly with Velcro®, and no significant change in dive depth was observed for either treatment compared to the control. Stroke frequency was significantly greater compared to the control at the end of the trial for the Velcro® attachment only, although there was no corresponding increase in swimming speed. This information can be used to design effective approaches for actively tracking free-ranging hatchling sea turtles to understand dispersal and survival of these vulnerable marine species.